Lab-scale siRNA and mRNA LNP manufacturing by various microfluidic mixing techniques - an evaluation of particle properties and efficiency - David C. Jürgens; Leonie Deßloch; Diana Porras-Gonzalez; Joshua Winkeljann; Sebastian Zielinski; Matthias Munschauer; Andreas L. Hörner; Gerald Burgstaller; Benjamin Winkeljann; Olivia M. Merkel (Elsevier, 2023)
Lipid Nanoparticles (LNPs) are promising drug delivery systems for various RNAs such as small interfering (siRNA) and messenger RNA (mRNA). Microfluidic mixing is a common technique to encapsulate RNA in LNPs. However, high flow rates and lipid concentrations are used for LNP formation to control LNP size as well as RNA encapsulation efficiency. We investigated the feasibility of downscaling siRNA and mRNA LNP manufacturing to save materials and enable a broader access to this technology. To optimize such a down-scaled procedure, we evaluated physicochemical nanoparticle characteristics including hydrodynamic diameter, zeta potential, particle concentration, encapsulation efficiency, and recovery for LNPs produced with three different microfluidic methods. We observed differences in nanoparticle characteristics and in vitro performance regarding cellular uptake, gene silencing, and mRNA expression. We determined the gene knockdown ability of the best siRNA LNPs formulation ex vivo using precision-cut lung slices to highlight the translational character of LNPs for inhalation and observed comparable efficacy as with a commercially available transfection reagent.